2019
DOI: 10.1002/pits.22283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibullying programs on teachers’ interventions in bullying situations. A meta‐analysis

Abstract: Even though teachers are key figures of a program's effectiveness, most intervention studies have not focused explicitly on the effects of antibullying programs at teacher level. We conducted a meta‐analysis into the effects of school‐based antibullying programs on determinants of teacher intervention, including teachers’ attitudes towards bullying, their self‐efficacy and knowledge regarding intervention strategies, and the effects on teachers’ bullying intervention itself. Following the PRISMA guidelines, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 70 publications
(98 reference statements)
0
21
0
1
Order By: Relevance
“…Based on these considerations, our study seems to emphasize the importance of making teachers’ actions more frequent, effective and visible for pupils, since it is very crucial that teachers can be a trusted point of reference for dealing with bullying, especially for victims [ 57 ]. In addition, as revealed by a recent meta-analysis [ 7 ], although teachers are involved in the bullying phenomena, most studies have not analyzed the possible effects of anti-bullying programs on teachers’ intervention practices. However, even if anti-bullying programs can improve teachers’ self-efficacy in dealing with bullying, as well as their knowledge of the phenomenon, when students’ perceptions of their teachers in dealing with bullying have been analyzed [ 7 ], only small effects have been found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on these considerations, our study seems to emphasize the importance of making teachers’ actions more frequent, effective and visible for pupils, since it is very crucial that teachers can be a trusted point of reference for dealing with bullying, especially for victims [ 57 ]. In addition, as revealed by a recent meta-analysis [ 7 ], although teachers are involved in the bullying phenomena, most studies have not analyzed the possible effects of anti-bullying programs on teachers’ intervention practices. However, even if anti-bullying programs can improve teachers’ self-efficacy in dealing with bullying, as well as their knowledge of the phenomenon, when students’ perceptions of their teachers in dealing with bullying have been analyzed [ 7 ], only small effects have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bullying is a risk factor for suicide attempts among adolescents globally, as revealed by a recent study involving 48 countries [5], which showed that the prevalence of suicide attempts increased as a function of the frequency of bullying in the past month. Given the significance of the bullying phenomenon in society, it is not surprising that many scholars have dedicated their efforts to setting up and evaluating the effectiveness of anti-bullying interventions (for a meta-analytical review [6]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the education community, training and prevention actions must be implemented to involve families and all community members [39]. A number of authors have carried out multiple studies based on the effect of intervention programmes to reduce bullying prevalence with students [40,41], with students and teachers [42,43], and with family intervention [39,44,45]. Nevertheless, very few studies have focused on improving the cohesion levels of students through the promotion of language proficiency.…”
Section: Studies Related To Anti-bullying Programmes and Programmes Tmentioning
confidence: 99%